196 The effect of affect: what we teach our learners about the role of patient induced emotion in clinical reasoning in the ED and why?. Issue 12 (23rd November 2020) - Roy, Susie; Skinner, Janet; Jaap, Alan
Abstract : Aims/Objectives/Background: Few empirical studies explore the contribution of non-clinical factors to perceptions of patient difficulty in EM. Fewer have investigated what students placed in EDs learn about 'difficult' patients or what, if anything, clinicians teach about the topic. We looked to address this. Considering these questions is imperative: patients perceived as frustrating report lower satisfaction with their clinical encounter, experience worse health outcomes and seem to be at risk of medical error secondary to faulty clinical reasoning. Methods/Design: With ethical approval, we undertook three interrelated, qualitative studies to conduct a case study of the undergraduate EM module delivered at Edinburgh University. In the first two, focus groups were used as the method of data collection; five clinician (n=25) and four medical student (n=21) groups were facilitated. In the third, semi-structured interviews with clinicians (n=12) were conducted. All groups/interviews were audio-recorded and transcribed. The data were analysed inductively using reflexive thematic analysis. Results/Conclusions: Frequent attendance, demands, pre-existing relationships and unrealistic expectations contributed to perceived patient difficulty. These were modified by personal and circumstantial factors. Although rarely told, students were aware who these 'difficult' patients were through observing behaviours. Critically, clinicians and students alike believed frustration adversely impacted aspects of clinical reasoning. Students struggled when witnessing what they considered 'bad' behaviour as it contradicted their previously held ideals of how physicians should act. It seems we teach students to try to internalise emotion yet that it is acceptable to let it negatively impact patient care. To combat this, students sought greater emotional transparency from physicians as well as advice on self-management strategies. Clinicians recognised the benefits of being candid but were afraid of being so. Contributing to this is the culture in medicine being one that mistrusts emotion. Further, both groups desired a formal curriculum addressing emotion in clinical reasoning thus suggesting one is needed.